Rural-Urban Labor Migration, Remittances, and Its Effect on Migrant-Sending Farm Households: Northwest Ethiopia - Haymanot Bassie; Teshome Sirany; Bizuayehu Alemu (Advances in Agriculture)
The purpose of this research is to examine the impact of rural-urban labor migration and remittances on rural agricultural productivity. A rigorous random selection process was used to pick 480 households from cross-sectional data. For this investigation, both primary and secondary data were used. Stata version 16 was used to examine both qualitative and quantitative data using descriptive (mean, standard deviation, and percentages) and econometric (three-stage least square technique) analyses. According to the descriptive data, the majority of respondents used their remittances for consumption, to acquire agricultural inputs, and to pay back their debts and tax payments. According to econometric studies, rural-urban migration has little influence on agricultural productivity. Remittances, cultivated land, livestock ownership, and extension services, on the other hand, have a positive and significant effect on agricultural productivity. In a nutshell, the link between migration, remittances, and agricultural output in agrarian and rural families is remarkable. Agriculture is the major source of income and mostly handles the liquidity issue. Agriculture production in the study region is labor intensive, and it is influenced by the amount of effort utilized in production as well as the socioeconomic characteristics of the household. As a result, it must address the major conundrum of agricultural productivity, particularly rural-urban migration and remittances. Address a knowledge gap, begin activities, and develop and implement multiple initiatives by various responsible stakeholders that are essential for the research topic. Furthermore, agricultural extension service delivery should be improved by timely recruiting, frequent agent training, and appropriate logistics.